1980
DOI: 10.1111/j.1545-5300.1980.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Psychiatric Ward Treatment in India

Abstract: The evolution of family psychiatric ward treatment is reviewed with special reference to the developments at the National Institute of Mental Health and Neuro Sciences, Bangalore, India. The set-up and philosophy of the Family Psychiatric Center are highlighted. Case reports are included. The effects of the patient's preference to be accompanied by a particular relative during family ward treatment was studied. The patient's preference for a particular relative was determined by means of a questionnaire. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…As a result, patients are discharged much sooner, recovery was found to be more complete and durable with greater reduction of stigma (Bhatti et al 1980). In addition, a report from Qatar has shown that patients diagnosed as suffering from schizophrenia, residing in extended families, were seen earlier in their course of illness and had less likelihood of deteriorated, socially withdrawn courses, as compared with patients residing in nuclear families (El-Islam, 1979).…”
Section: Discussionmentioning
confidence: 93%
“…As a result, patients are discharged much sooner, recovery was found to be more complete and durable with greater reduction of stigma (Bhatti et al 1980). In addition, a report from Qatar has shown that patients diagnosed as suffering from schizophrenia, residing in extended families, were seen earlier in their course of illness and had less likelihood of deteriorated, socially withdrawn courses, as compared with patients residing in nuclear families (El-Islam, 1979).…”
Section: Discussionmentioning
confidence: 93%
“…[40] Subsequent work by researchers[41–43] showed the usefulness of involving families in the management of a variety of psychiatric disorders including marital discord, hysteria and psychosis. In the late 1980s, the center developed Indian tools for working in the field of family therapy, notable amongst which are the Family Interaction Pattern Scale, the Family Topology Scale[4445] and the Marital Quality Scale. [46] In the late 1980s and 1990s the center started training post graduates in psychiatry in concepts and schools of family therapy and started orienting itself to structured rather than generic family therapy.…”
Section: Understanding Psychotherapy From the Family Perspectivementioning
confidence: 99%
“…The family therapy unit at our centre has been functioning for a decade now, and a description of its organisation and philosophy has been reported earlier (Bhatti et al 1980). In India, the need to involve the family of the patient in treatment is beyond dispute but the degree to which the family members may need to be involved is likely to vary.…”
Section: Introductionmentioning
confidence: 98%